2006
DOI: 10.1200/jco.2005.03.5279
|View full text |Cite
|
Sign up to set email alerts
|

11C-Acetate Positron Emission Tomography Imaging and Image Fusion With Computed Tomography and Magnetic Resonance Imaging in Patients With Recurrent Prostate Cancer

Abstract: Retrospective fusion of AC PET and CT/MRI is feasible and seems to be essential for final diagnosis. This is particularly true in patients with AC uptake in the prostate region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 23 publications
1
62
1
4
Order By: Relevance
“…Unfortunately, the most commonly available tracer, 18 F-labeled glucose ( 18 F-FDG), has a low sensitivity for cancer detection (7). Although preliminary studies have demonstrated that 11 C-acetate is a promising tracer for diagnosis of recurrent (8)(9)(10) or metastatic (11) prostate cancer, its use in primary diagnosis is less well established. In particular, the clinical role of 11 C-acetate in prostate cancer detection and staging is currently unclear (12,13).…”
mentioning
confidence: 99%
“…Unfortunately, the most commonly available tracer, 18 F-labeled glucose ( 18 F-FDG), has a low sensitivity for cancer detection (7). Although preliminary studies have demonstrated that 11 C-acetate is a promising tracer for diagnosis of recurrent (8)(9)(10) or metastatic (11) prostate cancer, its use in primary diagnosis is less well established. In particular, the clinical role of 11 C-acetate in prostate cancer detection and staging is currently unclear (12,13).…”
mentioning
confidence: 99%
“…The most common tracer, 2 [ 18 F]fluoro-2-deoxy-D-glucose (FDG), has a low sensitivity for detecting early prostate cancer due to the low glucose consumption (9,10), limiting the possibility to detect clinically localized disease. Other tracers, such as 18 F-or 11 C-labeled choline and [ 11 C]-acetate, are used mainly for the diagnosis of recurrent (11)(12)(13) or metastatic (14) prostate cancer. Their feasibility in primary diagnosis is limited because of uptake in benign tissue such as benign prostatic hyperplasia (BPH; refs.…”
Section: Introductionmentioning
confidence: 99%
“…11 C-acetate, 11 C-choline, and 18 F-choline have been reported to be useful for the diagnosis of recurrent or metastatic prostate cancer (4)(5)(6)(7)(8). However, the very short half-life of 11 C limits its use to facilities equipped with a cyclotron.…”
mentioning
confidence: 99%